T1 Mapping - Aplicações Cardíacas - Diogo Plasencia e Quelhas (2022)
Introduction: Cardiac magnetic resonance is a non-invasive method for the diagnosis and follow-up of diseases of the cardiovascular system. The most recent advances have allowed for the development of T1 mapping, a technique that can identify small tissue variances. Due to its potential and recent development, this technique may gain more and more importance. As such, it is essential to understand T1 mapping's basic principles. This review has the objective of analyzing this technique and its possible applications in heart diseases. Methods: In November 2021, a search was made in the database MEDLINE (PubMed), using the following query: "T1 Mapping" AND "CMR. Results: The main cardiac magnetic resonance sequences can be divided according to two groups: study of morphology and function and myocardial tissue characterization. For the latter, T2-weighting, late gadolinium enhancement, T2 and T2* mapping and T1 mapping are used. T1 mapping relies on MOLLI, shMOLLI, and SASHA sequences for imaging. Lastly, this technique has shown potential in the diagnosis of ischemic and non-ischemic pathologies. Discussion: T1 mapping is a promising technique in the correlation of the most common pathologic processes in cardiovascular disease. While this procedure's potential for the future of cardiac magnetic resonance is remarkable, as far as diagnosis and prognosis are concerned, it is essential to indicate that there is still work to be done regarding standardization of the different techniques and protocols.